BRINGING MIL INTO THE MARGINS: INTRODUCING MEDIA AND INFORMATION LITERACY AT THE OUTSKIRTS - Manabat, April (International Journal of Media and Information Literacy, 2021)
With the vast amount of information readily available online, not to mention the gaining popularity and use of social media platforms and the rampant proliferation of alternative facts and news fabrication that affects decision-making, it is indeed empirical for everyone to be media and information literate. More true in it sense, people living in areas with limited or no internet access at all should be more critical and analytical about every information they encounter as this may affect their perspectives on things and life in general. This paper documents how media and information literacy was promoted and introduced to selected Senior High School (SHS) students and teachers of Loyola College of Culion (LCC) in Isla Culion, Palawan, Philippines. Theeffectiveness of the seminar-workshops conducted among the participants was also determined as well as their working knowledge on MIL through some tests and group activities. This case study also revealed that the participants’ working knowledge has increased after being exposed to the lectures and activities. Furthermore, the participants highlighted how they found MIL valuable in critically evaluating sources of information and how to use social media responsibly. In addition, the participants found the seminar-workshop engaging and recommended to have more sessions like this in improved in the future.
Keywords: media and information literacy; Isla Culion; Palawan; Philippines; Type of access: Open Access